Resultados parciales Plasticizer polyols/mfc films production for single-use primary food packaging - Ehman, Nanci Vanesa (2023)
This study evaluated the changes in physical, mechanical, optical, and barrier properties of microfibrillated cellulose (MFC) films whit food-grade polyols addition. MFC was obtained from pine sawdust pulp using a simple disk refiner. The films were acquired by solvent casting mixing 75%w/w MFC and 25% w/w of three polyols (sorbitol, mannitol, and glycerol) and dried at 50°C. The characterization included: physical-mechanical properties, optical behavior, and water vapor permeability (WVP). Finally, the aerobic biodegradation in soil of films was evaluated (15 days period).